Breast cancer vaccines: Heeding the lessons of the past to guide a path forward. (March 2020) - Solinas, Cinzia; Aiello, Marco; Migliori, Edoardo; Willard-Gallo, Karen; Emens, Leisha A.
Highlights: No vaccine has yet been approved for either breast cancer treatment or prevention. No significant clinical benefit from breast cancer vaccines was seen in the metastatic or adjuvant setting. Patient selection, delivery routes, timing, combination and/or sequence with other therapies would improve efficacy of vaccines in breast cancer. Personalized treatments would increase the efficacy of immunotherapy in breast cancer. Abstract: The ability of cancer immunotherapy to generate lasting responses in a broad spectrum of tumors has generated great enthusiasm in medical oncology. A number of new immune-based compounds have now been approved based on the recent success of immune checkpoint blockade, either administered as monotherapy or in combination with other agents. Because clinical activity is limited only to subsets of patients, two major goals of cancer immunotherapy are (1) to reliably identify responders to these current treatments, and (2) to increase the number of patients who can respond to immunotherapy by developing new strategies. These goals are critically important since the hallmark of immune-based therapies is the induction of durable immunologic and clinical responses that result in overall survival benefit. Innovative combination strategies have great potential for bringing the benefit of immunotherapy to more patients. The use of cancer vaccines to actively induce immune effectors together with other drugs, which may include immune checkpoint blockade, chemotherapy, and/or molecularly targeted agents, is a particularly attractive strategy. Cancer vaccines have been tested both to prevent or intercept the development of cancer, and to decrease established tumor burdens. No vaccine has yet been approved for either breast cancer treatment or prevention. Here, we review the history of breast cancer vaccine development, and highlight near-term opportunities for moving forward.